FORENSIC INVESTIGATION Of THE SAMARINDA IBU dan ANAK HOSPITAL BUILDING: STRUCTURAL SETTLEMENT ANALYSIS - Efendi, Aco Wahyudi (JURNAL RIVET, 2024)
In initiatives to enhance the quality of infrastructure, especially with regard to building stability and the avoidance of structural failure, the safety and comfort of visitors has taken center stage. In order to improve infrastructure, older or decaying buildings are frequently reinforced or renovated. This may entail repairing accumulated damage without requiring total demolition. In order to guarantee the structure's dependability and safety, these remodeling initiatives require careful assessment and study. Concerns over apparent settlement of the Ibu dan Anak Hospital building in Samarinda have been brought up, highlighting the significance of assessing structural integrity to guarantee ongoing safety and functionality. The purpose of this study is to conduct a thorough structural audit of the building in order to find any possible hazards and suggest any necessary improvements. The study assessment the building's stability and forecasts future settlement by simulating its behavior under various circumstances, including dynamic and static load scenarios, using sophisticated modeling software such as GEOSLOPE-GEOSTUDIO (Student Version). According to the aforementioned analytical results, there are signs that the hard soil layer is not reached by the pile depth, which causes settlement. Over the course of the following year, the settlement increased from 15.89 cm in the first 178 days to 17.64 cm. The analysis indicates that the settlement will stay at 31.65 cm for the next five years, therefore after 1,780 days, it is deemed stable.